Housing fever in Australia 2020-23: Insights from an econometric thermometer - SHI, Shuping (Institutional Knowledge at Singapore Management University, 2023)
Australian housing markets experienced widespread and, in some cases, extraordinary growth in prices between 2020 and 2023. Using recently developed methodology that accounts for fundamental economic drivers, we assess the existence and degree of speculative behaviour, as well as the timing of exuberance and downturns in these markets. Our findings indicate that speculative behaviour was indeed present in six of the eight capital cities at some time over the period studied. The sequence of events in this nation-wide housing bubble began in the Brisbane market and concluded in Melbourne, Canberra, and Hobart following the interest rate rise implemented by the Reserve Bank of Australia in May 2022. As of March 2023, the housing markets in Sydney, Canberra and Hobart had broadly regained stability, while Melbourne's return to its normal state is more gradual. In addition, over-corrections against fundamentals are evident in the housing markets of Brisbane, Adelaide, Darwin and Perth.